Pengaruh Tata Kelola Perusahaan dan Penghindaran Pajak Terhadap Manajemen Laba Pada Perusahaan Manufaktur di Indonesia - Juoro Larastomo; Halim Dedy Perdana; Hanung Triatmoko; Eko Arief Sudaryono (Faculty of Economic and Business, 2016)
The Impact of Corporate Governance and Tax Avoidance on Earning Management at Indonesian Manufacturing CompaniesThe objective of this study is to determine the impact of corporate governance and tax avoidance on earning management by Indonesian manufacturing companies listed on IDX in 2010-204. This study used board of commissioner, independent commissioner, audit committee, and managerial ownership as corporate governance’s variabel. Population of this study is Indonesian manufacturing companies listed on IDX in 2010-2014. Sample of this study are 21 companies that generated using purposive sampling method. The multiple regression analysis test showed that board of commissioner, independent commissioner and tax avoidance have positive impact on earning management. But, managerial ownership has positive impact on earning management and audit committee has no impact on earning managementDOI: 10.15408/ess.v6i1.3121